Types of Fixed Points of Set-Valued Contraction Mappings for Comparable Elements - Latif, Shaimia Qais; Abed, Salwa Salman (Iraqi Journal of Science, 2020)
This paper is concerned with the study of the fixed points of set-valued contractions on ordered metric spaces. The first part of the paper deals with the existence of fixed points for these mappings where the contraction condition is assumed for comparable variables. A coupled fixed point theorem is also established in the second part.